Biological characteristics of a sub-population of cancer stem cells from two triple-negative breast tumour cell lines - Enciso-Benavides, J. (2021)
Triple-negative breast tumours (TNBTs) make up 15-20% of all breast tumours. There is no treatment for them, and the role that cancer stem cells (CSCs) have in carcinogenesis is still unclear, so finding markers and therapeutic targets in CSC exosomes requires these cells to exist as a homogeneous cell population. The objective of this work was to determine differences in ultrastructural morphology, proliferative capacity, and mouse-xenotransplantation characteristics of the MDA-MB-231 and MDA-MB-436 TNBT cell lines with the CD44 high /CD24 low phenotype in order to study their exosomes. The results show that the CD44 high /CD24 low MBA-MB-231 cells had a population doubling time of 41.56 h, compared to 44.79 h in the MDA-MB-436 cell line. After magnetic immunoseparation, 18.75% and 14.56% of the stem cell population of the MDA-MB-231 and MDA-MB-436 cell lines, respectively, were of the CD44 high /CD24 low phenotype, which were expanded to reach purities of 80.4% and 87.6%. The same expanded lineage in both cell lines was shown to possess the pluripotency markers Nanog and Oct4. Under a scanning electron microscope, the CD44 high /CD24 low lineage of the MBA-MD-231 cell line formed groups of more interconnected cells than this lineage of the MBA-MD-436 line. A total of 16% of the mice inoculated with the CD44 high /CD24 low lineage of either cell line presented tumours of the breast, lung, and submandibular ganglia, in whose tissues variable numbers of inoculated cells were found 30 days post-inoculation. By magnetic immunoselection, it was possible to isolate in similar quantities and characterize, expand, and xenotransplant the CD44 high /CD24 low lineage of the MDA-MB-231 and MDA-MB-436 cell lines. The former cell line has greater proliferative capacity, the two lines differ under scanning electron microscopy in how they intercommunicate, and both cell lines induce new tumours in mice and persist at least 30 days post-inoculation in the transplanted animal so their exosomes would also be different.